2018
DOI: 10.4314/gjds.v15i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Access to Trade Credit by Informal Firms in Ghana: Does Locating in Industrial Cluster and Holding Production/Supply Contract Matter?

Abstract: The paper examines the effect of locating in industrial cluster and holding production/ supply contract on access to trade credit by informal firms in Ghana. It employs data from the 2013 World Bank survey of informal firms in Ghana. The results show that trade credit is the most important external source of financing working capital for firms in the informal sector. Binary probit was employed in the econometric analysis. Controlling for firm characteristics, financial characteristics, firms' largest owners' c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The results show that agricultural trade credit activity, whether advance payment or sales of good on credit (trade credit receivable), is driven by a multiplicity of factors and not a single factor. The finding that holding a preharvest production and sales contract increases the probability of receiving advance payment is consistent with the findings of Dary (2018) in the informal sector in Ghana. In the study, holding supply or production contracts was significantly associated with the receipt of trade credit from buyers.…”
Section: Discussionsupporting
confidence: 87%
“…The results show that agricultural trade credit activity, whether advance payment or sales of good on credit (trade credit receivable), is driven by a multiplicity of factors and not a single factor. The finding that holding a preharvest production and sales contract increases the probability of receiving advance payment is consistent with the findings of Dary (2018) in the informal sector in Ghana. In the study, holding supply or production contracts was significantly associated with the receipt of trade credit from buyers.…”
Section: Discussionsupporting
confidence: 87%
“…In order to measure corporate reputation, firm size is used as its proxy (Akabayashi et al , 2005; Lin et al , 2015, 2016; Dary, 2018). The information on total assets (in Rs.…”
Section: Research Methodology and Data Collectionmentioning
confidence: 99%
“…It is widely documented in past research that firm size serves as a conspicuous signal and that large firms are expected to be viewed favorably by stakeholders. Reputation is a hard-to-measure construct and following the approach of Akabayashi et al (2005), Lin et al (2015, 2016) and Dary (2018), firm size is deployed as a proxy for corporate reputation in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hermes et al (2012) find a negative impact of trade credit on the switching behaviour of customers in the rice market of Tanzania implying that trade credit acted as a barrier when customers decided to switch to another supplier. However, Dary (2018) reported a positive impact of trade credit on the working capital of informal firms in Ghana. Likewise, Mubashar et al (2018) observed that trade credit relationship was important for short term financing.…”
Section: Introductionmentioning
confidence: 97%